Comparative Characteristics of Determination of Antioxidant Activity of Sea Buckthorn Fruits by Various Methods - O. V. Trineeva (Разработка и регистрация лекарственных средств, 2019)
Introduction. Recently, much attention has been paid to the primary assessment of the pharmacological effect of various drugs using in vivo and in vitro tests. It is known that such a medicinal plant as sea buckthorn, in its phytochemical composition is rich in natural antioxidants: carotenoids, tocopherols, flavonoids, ascorbic acid, etc. In some publications there is information about the antioxidant activity of sea buckthorn and fatty oil based on them. However, information on the comparative characteristics of the use of various methods for determining the antioxidant activity of this type of medicinal plant material and the results obtained are not found in the scientific literature.Aim. The aim of this work was a comparative determination of the antioxidant activity of medicinal plant material of buckthorn fruits of various species of buckthorn.Materials and methods. The total antioxidant activity of water and water-alcohol extracts from the fruits of sea buckthorn fruits was determined using various techniques recommended in the literature. The antioxidant activity of the extracts was determined by permanganometric titration, in vitro inhibition of adrenaline autooxidation, and also in a biological model, Parametium caudatum cell culture.Results and discussion. The effect of the extractant polarity on the value of antioxidant activity was studied. It was found that the highest content of antioxidants in the extraction is observed when using 96 % ethanol as an extractant.Conclusion. Using three methods, the prospects of using sea buckthorn fruits and preparations based on them as a source of antioxidants are shown.